Insulation between adjacent TADs is controlled by the width of their boundaries through distinct mechanisms - Andrea Papale; Julie Segueni; Hanae El Maroufi; Daan Noordermeer; David Holcman (Proceedings of the National Academy of Sciences, 2025)
Topologically associating domains (TADs) are sub-Megabase regions in vertebrate genomes with enriched intradomain interactions that restrict enhancer–promoter contacts across their boundaries. However, the mechanisms that separate TADs remain incompletely understood. Most boundaries between TADs contain CTCF binding sites (CBSs), which individually contribute to the blocking of Cohesin-mediated loop extrusion. Using genome-wide classification, here we show that the width of TAD boundaries forms a continuum from narrow to highly extended and correlates with CBSs distribution, chromatin features, and gene regulatory elements. To investigate how these boundary widths emerge, we modified the random crosslinker polymer model to incorporate specific boundary configurations, enabling us to evaluate the differential impact of boundary composition on TAD insulation. Our analysis, using three generic boundary categories, identifies differential influence on TAD insulation, with varying local and distal effects on neighboring domains. Notably, we find that increasing boundary width reduces long-range inter-TAD contacts, as confirmed by Hi-C data. While blocking loop extrusion at boundaries indirectly promotes spurious intermingling of neighboring TADs, extended boundaries counteract this effect, emphasizing their role in establishing genome organization. In conclusion, TAD boundary width not only enhances the efficiency of loop extrusion blocking but may also modulate enhancer–promoter contacts over long distances across TAD boundaries, providing a further mechanism for transcriptional regulation.